Managing rapport in the context of classroom talk: A case study of a London secondary school (Journal of Applied Learning and Teaching, 2019)
Recently, the research on classroom conflict talk has attracted much attention from applied linguistics scholars. However, how the teacher uses language to effectively resolve conflict while striking a balance between achieving their own and their students’ objectives, has not been fully researched to date. Acknowledging this gap, this paper investigates a conflict classroom talk between a teacher and a group of students in a Mandarin lesson at a secondary school in London. Its analysis drew on the framework of rapport management to explore how the teacher and students negotiated and achieved their respective goals and tasks while maintaining the teacher-student relationship within this particular institutional setting. For the purpose of this study, Conversation Analysis, as a very fine tool, was employed to present diverse features and in-depth details, such as redirection and minimal acknowledgment. It found that although a perceived unbalance of power exists between teachers and students, students in this study broke the asymmetry and made themselves heard, which in turn became what the teacher valued highly in the class.